Preoperative biliary drainage in resectable pancreatic cancer: a systematic review and network meta-analysis. Issue 6 (June 2018) - Lee, Peter J.; Podugu, Amareshwar; Wu, Dong; Lee, Arier C.; Stevens, Tyler; Windsor, John A.
Abstract: Background: Controversy remains about the best pre-operative management of jaundice in patients with resectable pancreatic head cancer (RPC) undergoing planned pancreaticoduodenectomy (PD). Objective: The aim of this study was to compare rates of post-operative complications in patients undergoing four pre-operative approaches (POA): preoperative biliary drainage with plastic stent (PBD-PS), metal stent (PBD-MS), and percutaneous transhepatic drain (PBD-PT), or no pre-operative biliary drainage (NPBD). Method: A study was included in the systematic review if it assessed the effects of PBD on post-operative outcomes in jaundiced patients with RPC. Endpoints were the rate of any post-operative complication, wound infection, intra-abdominal infection and post-operative bleeding. A network meta-analysis (NMA) was performed to rank the POAs from the best to worst, for each outcome. Results: Thirty-two studies were included in the systematic review. Ten out of 32 studies included in the systematic review reported at least one of the 4 outcomes of interest and thus were used for NMA. The calculated odds ratios and P-scores ranked NPBD as the best approach. There was insufficient evidence to determine the best modality of PBD among PBD-PS, PBD-MS and PBD-PT. Conclusions: No preoperative biliary drainage may be the best management of preoperative jaundice in patients with RPC before PD. Further studies are needed to determine the best modality in patients that need PBD.